Evolution of the legal regulation regarding administrative enforcement proceedings in Poland - Masternak, Marian (Studia Iuridica Toruniensia, 2024)
The subject of the article is the evolution of the legal regulation of administrative enforcement proceedings. The study discusses the various stages of the development of this regulation, thanks to which it was possible to show the process of shaping the currently functioning institutions of this procedure and to formulate de lege lata and de lege ferenda conclusions.